Back Cover: Phase‐Reversal Emulsion Catalysis with CNT–TiO2 Nanohybrids for the Selective Oxidation of Benzyl Alcohol (Chem. Eur. J. 48/2013). Issue 48 (25th November 2013) - Yu, Chang; Fan, Liman; Yang, Juan; Shan, Yuanyuan; Qiu, Jieshan
<x xml:space="preserve">Abstract</x> Carbon nanotube–TiO2 nanohybrids have been fabricated with a simple and efficient method that allows for control over the carbon nanotube content. In the Communication on page 16192 ff., J. Qiu et al. report on the use of these nanohybrids as phase‐reversal emulsion catalyst supports for ruthenium in the selective oxidation of benzyl alcohol to benzaldehyde.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>